Safety of cyclin-dependent kinase4/6 inhibitor combined with palliative radiotherapy in patients with metastatic breast cancer. (December 2021) - Kim, Kristine N.; Shah, Payal; Clark, Amy; Freedman, Gary M.; Dastgheyb, Sana; Barsky, Andrew R.; Dreyfuss, Alexandra D.; Taunk, Neil K.
Abstract: Introduction: Cyclin-dependent kinase (CDK)4/6 inhibitor is a first-line therapy for metastatic ER+/HER2-breast cancer. However, there are limited data on safety of combined radiotherapy (RT) and CDK4/6 inhibition. Methods: We conducted a retrospective study of women with metastatic breast cancer who received palliative RT within 14 days of CDK4/6 inhibitor use. The primary endpoint was toxicity per Common Terminology Criteria for Adverse Events v5. Secondary endpoints were pain response and local control based on clinical assessment and imaging. Results: Thirty patients underwent 36 RT courses with palbociclib (n = 34 courses, 94.4%) or abemaciclib (n = 2, 5.6%). RT was delivered before, concurrently or after CDK4/6 inhibitors in 7 (19.4%), 8 (22.2%), and 21 (58.3%) of cases with median 3.5 days from RT to closest CDK4/6 inhibitor administration. Median RT dose was 30Gy (range 8–40.05Gy). Treated sites included brain (n = 5, 11.6%), spine (n = 19, 44.2%), pelvis (n = 9, 20.9%), other bony sites (n = 6, 14.0%) and others (n = 4, 9.3%). No acute grade ≥3 non-hematologic toxicity occurred. No increased hematologic toxicity was attributable to RT with grade 3 hematologic toxicities rates 16.7%, 0%, and 6.7% before, during, and 2 weeks after RT completion. All but one patient (29/30) achieved symptom relief. Local control rates were 94.4%, 91.7% at 6 and 12 months. Conclusions: The use of RT within 2 weeks of CDK4/6 inhibitors had low acceptable toxicity and high efficacy, suggesting that it is safe for palliation of metastatic breast cancer. Highlights: CDK4/6 inhibitors with endocrine therapy is a preferred first line therapy for HR+, HER2-metastatic breast cancer. Limited data exists on safety of combined radiotherapy and CDK4/6 inhibition in patients with metastatic breast cancer. This retrospective cohort study included 30 patients who underwent palliative RT with combined CDK4/6 inhibitor use. RT within 2 weeks of CDK4/6 inhibitor had low toxicity and high efficacy, supporting its safety in metastatic breast cancer.